Mobile first journalism : producing news for social and interactive media - Hill, Steve (Routledge, 2019)
Media publishers produce news for a full range of smart devices – including smartphones, tablets and watches. Combining theory and practice, Mobile-First Journalism examines how audiences view, share and engage with journalism on internet-connected devices and through social media platforms.